Paeoniflorin Attenuated TREM-1-Mediated Inflammation in THP-1 Cells. (18th April 2022) - Cao, Li; Yang, Kerong
Abstract : Sepsis is caused by bacterial infections or viral infections. Clinically, there exist confirmed or highly suspected infection foci. Mortality caused by septic shock remains in a high rate even though antibiotic treatment works effectively. In this study, we treat THP-1 cells with 1 ug/mL LPS (lipopolysaccharide) and add paeoniflorin or LR-12 inhibitor. TREM-1 (triggering receptor expressed on myeloid cells-1), IL-6, IL-1 β, and TNF- α (tumour necrosis factor alpha (a)-cachectin) were detected by ELISA and qRT-PCR, and western blotting is performed to detect related proteins in the NF- κ B signaling pathway. As a result, paeoniflorin can significantly reduce the production of LPS-stimulated TREM-1 as well as inflammatory factors and attenuate the phosphorylation of NF- κ B signaling pathway-related factors, such as p65 and I κ B α . At the same time, the combined effect of paeoniflorin and LR-12 is more significant. The results of this study solidly prove that paeoniflorin plays a role in inhibiting TREM-1-mediated inflammation and the NF- κ B pathway could be a potential mechanism of action.